El problema de bancarrota - Huaman Alfaro, Josep Antenor (2024)
The bankruptcy problem represents a common challenge across various fields, from the allocation of limited resources to the liquidation of assets in cases of bankruptcy. This research explores how to divide resources fairly and efficiently when they are insufficient to fully meet the claims of all creditors or claimants. Using an axiomatic approach, classical solutions to bankruptcy problems such as the proportional rule, the equal awards rule, the equal losses rule, the Talmud rule, and the random arrival rule are reviewed and compared. Additionally, we address the bankruptcy problem from a cooperative game perspective, exploring the relationship between these game solutions and bankruptcy rules. We extend our basic model to a discrete model, where the asset to be divided and the creditors’ claims are represented by integers. Due to these indivisibilities, the objective is to develop and analyze rules that address these situations in a fair and efficient manner, resolved through the comparison standard. Finally, a non-cooperative investment game is constructed to analyze the implications of these principles on investment behavior in bankruptcy scenarios.